Catalytic cooperation between Ru and Pd atoms on hierarchical porous Ce-based oxide for boosting engine exhaust purification - Linsheng Xu; Tian Qin; Yuanfeng Li; Hao Guo; Qiao Hu; Jing Xiong; Yaxiao Ma; Peng Zhang; Xiaolin Yu; Xi Liu; Yunpeng Liu; Zhen Zhao; et al. (Nature Communications)
Abstract Simultaneous oxidation of soot and CH4 emitted from natural gas-diesel dual fuel engine is a new challenge. Herein, a robust catalyst of binary Ru-Pd components supported on three-dimensional ordered macro-mesoporous cerium-zirconium oxide (RuPd/3DOMM-CZO) is elaborately constructed. Ordered macro-mesopore structure in novel hierarchical porous cerium-zirconium oxide can respectively enhance mass transfer of soot and gaseous reactants, and binary Ru-Pd active components can improve activation for NO and CH4. RuPd/3DOMM-CZO catalyst exhibits excellent catalytic performance and stability during simultaneous soot and CH4 oxidation. Based on the results of characterizations and theoretical calculations, Ru site in binary Ru-Pd components is responsible for catalyzing NO oxidation to NO2, which is key step of NOx-assisted soot oxidation mechanism, while Pd site can activate the C-H bond of CH4 for boosting oxidation to CO2; the catalytic cooperation between Ru and Pd atoms can promote the rate-determining step to realize simultaneous oxidation of soot and CH4.